Vagus nerve stimulation as immunomodulatory therapy for stroke: A comprehensive review - Jelinek, Matyas; Lipkova, Jolana; Duris, Kamil (Experimental neurology, 2024)
Stroke is a devastating cerebrovascular pathology with high morbidity and mortality. Inflammation plays a central role in the pathophysiology of stroke. Vagus nerve stimulation (VNS) is a promising immunomodulatory method that has shown positive effects in stroke treatment, including neuroprotection, anti-apoptosis, anti-inflammation, antioxidation, reduced infarct volume, improved neurological scores, and promotion of M2 microglial polarization. In this review, we summarize the current knowledge about the vagus nerve's immunomodulatory effects through the cholinergic anti-inflammatory pathway (CAP) and provide a comprehensive assessment of the available experimental literature focusing on the use of VNS in stroke treatment.
Keywords: cévní mozková příhoda; Vagus Nerve Stimulation; Vagus Nerve; vagová stimulace; lidé; nervus vagus; Antioxidants; Microglia; imunomodulace; Stroke; mikroglie; Immunomodulation; antioxidancia; Humans